Switching paradigms: transformative changes in film consumption patterns in the streaming era / Jayabarthi Manimaran - Manimaran, Jayabarthi; Abdul Hamid, Maizurah Khathu (Faculty of Communication and Media Studies (FCMS), 2024)
As of 2024, the impact of COVID-19 on cinema is still being felt, but the industry has largely adapted to the changes ushered in by the pandemic. This post - pandemic significantly altered global entertainment consumption, particularly the movie industry. This study examines how young adults’ movie consumption patterns shifted from traditional cinemas to Over-theTop (OTT) platforms as it continues from the post-pandemic trend. The research explores the influence of factors such as cost, convenience and preferences for OTT services over cinemas. Survey findings indicate that cinema ticket prices, which are perceived as higher compared to the affordable subscription models of OTT platforms, play a key role in shaping consumption choices. Additionally, the convenience of watching movies on personal devices and the ability to binge-watch content were prominent reasons for the popularity of OTT services. Despite cinemas reopening, the cinema industry has struggled to regain pre-pandemic audience levels. This research suggests that cinema operators may need to adjust their pricing strategies and explore hybrid release models in collaboration with OTT platforms to remain competitive. The study highlights the continued dominance of OTT platforms and calls for industry adaptation to meet the evolving demands of young audiences, offering valuable insights for both cinema and streaming services in a post-pandemic landscape.